2021
DOI: 10.18632/aging.203110
|View full text |Cite
|
Sign up to set email alerts
|

Cdkn1a transcript variant 2 is a marker of aging and cellular senescence

Abstract: Cellular senescence is a cell fate response characterized by a permanent cell cycle arrest driven primarily the by cell cycle inhibitor and tumor suppressor proteins p16 Ink4a and p21 Cip1/Waf1 . In mice, the p21 Cip1/Waf1 encoding locus, Cdkn1a , is known to generate two transcripts that produce identical proteins, but one of these transcript variants is poorly characterized. We show that the Cdkn1a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 23 publications
3
38
0
Order By: Relevance
“…These data demonstrated that although radiation induced both transgenes in bone and AP20187 cleared p21 Cip1 -and p16 Ink4a -expressing cells (which also expressed Egfp), senescent osteocytes, assessed using the TAF assay(Chandra et al, 2020;Farr et al, 2016), were only reduced in the p21-ATTAC mice. These data further demonstrate that although both our transgene promoters and the endogenous p21 Cip1 and p16 Ink4a promoters are upregulated following radiation(Chandra et al, 2020;López-Domínguez et al, 2021), it is p21 Cip1 that drives senescence in radiation-induced bone damage. Clearance of these cells prevents osteocyte senescence and the downstream consequences (i.e., increased SASP and bone loss).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…These data demonstrated that although radiation induced both transgenes in bone and AP20187 cleared p21 Cip1 -and p16 Ink4a -expressing cells (which also expressed Egfp), senescent osteocytes, assessed using the TAF assay(Chandra et al, 2020;Farr et al, 2016), were only reduced in the p21-ATTAC mice. These data further demonstrate that although both our transgene promoters and the endogenous p21 Cip1 and p16 Ink4a promoters are upregulated following radiation(Chandra et al, 2020;López-Domínguez et al, 2021), it is p21 Cip1 that drives senescence in radiation-induced bone damage. Clearance of these cells prevents osteocyte senescence and the downstream consequences (i.e., increased SASP and bone loss).…”
supporting
confidence: 56%
“…does differ following radiation both in vitro (López-Domínguez et al, 2021) and in vivo (Chandra et al, 2020). Thus, in cultured mouse dermal fibroblasts, levels of p21 Cip1 mRNA were induced within 3 h of radiation, whereas p16 Ink4a transcripts increased much later, ~50-h post-radiation (López-Domínguez et al, 2021).…”
Section: Further Characterization Of P21 Cip1 + Cells Following Radia...mentioning
confidence: 91%
“…Upregulation of p16/p19 and p21 is widely accepted as a marker of aging and senescence [16,[72][73][74]. In human tissue samples, P16 was detected in endocrine and exocrine pancreas, skin, kidneys, liver, intestine, spleen, brain, and lung.…”
Section: Discussionmentioning
confidence: 99%
“…The histone acetyltransferase KAT7, a genetic and epigenetic marker of senescence, is upregulated in murine models of ageing [28]. Cdkn1a transcript variant 2 is accumulated and activated during ageing and could be used for the diagnosis of ageing-related diseases [29].…”
Section: Hallmarks Of Cellular Senescencementioning
confidence: 99%